2021
DOI: 10.3390/ijms22116073
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Physiological Role of Transthyretin in Glucose Metabolism in the Liver

Abstract: Transthyretin (TTR), a 55 kDa evolutionarily conserved protein, presents altered levels in several conditions, including malnutrition, inflammation, diabetes, and Alzheimer’s Disease. It has been shown that TTR is involved in several functions, such as insulin release from pancreatic β-cells, recovery of blood glucose and glucagon levels of the islets of Langerhans, food intake, and body weight. Here, the role of TTR in hepatic glucose metabolism was explored by studying the levels of glucose in mice with diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 67 publications
0
1
0
Order By: Relevance
“…Interestingly, a large genotypic and phenotypic analysis conducted in humans showed an association between low TTR hepatic expression and lower body height (Pathak et al., 2022 ). Increased TTR expression also increases mitochondrial density whereas its insufficiency triggers a higher degree of oxidative phosphorylation in the liver (Alemi et al., 2021 ). The lower amount of TTR mRNAs in the liver of DCS‐resistant rats would therefore be coherent with the decrease in body weight observed in DCS‐resistant rats throughout the selection process (Lautridou, Buzzacott, et al., 2017 ), as well as with the hormonal and energetic remodeling (Vallée et al., 2021 ) and the lower basal mitochondrial oxygen consumption due to lower mitochondrial volume in skeletal muscle (Lautridou et al., 2020 ) that we previously reported in DCS‐resistance animals.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a large genotypic and phenotypic analysis conducted in humans showed an association between low TTR hepatic expression and lower body height (Pathak et al., 2022 ). Increased TTR expression also increases mitochondrial density whereas its insufficiency triggers a higher degree of oxidative phosphorylation in the liver (Alemi et al., 2021 ). The lower amount of TTR mRNAs in the liver of DCS‐resistant rats would therefore be coherent with the decrease in body weight observed in DCS‐resistant rats throughout the selection process (Lautridou, Buzzacott, et al., 2017 ), as well as with the hormonal and energetic remodeling (Vallée et al., 2021 ) and the lower basal mitochondrial oxygen consumption due to lower mitochondrial volume in skeletal muscle (Lautridou et al., 2020 ) that we previously reported in DCS‐resistance animals.…”
Section: Discussionmentioning
confidence: 99%
“…Transthyretin works by influencing the secretion of insulin and glucagon. 47 , 48 Moreover, it stabilizes the retinol-binding protein 4 (RBP4) at a higher steady-state concentration in circulation which eventually lead to insulin resistance. However, Jayaweera and colleagues showed that transthyretin can slow down the formation of islet amyloid polypeptide (IAPP).…”
Section: Discussionmentioning
confidence: 99%
“…Although most of it is synthesised in hepatocytes, a very small amount originates from tissues such as pancreas. 1 This protein is also known and named as transthyretin because of its thyroid hormones and vitamin A binding properties. 2 Prealbumin is a specific and sensitive marker of nutritional conditions.…”
Section: Introductionmentioning
confidence: 99%